Correlation of Sex Ratio and Population of Callosobruchus chinensis L. (Coleoptera: Bruchidae) in Mung Beans - Dinata, Gallyndra Fatkhu; Jihad, Baroroh Nur (Universitas PGRI Semarang, 2021)
One of the important pests on mung beans is the warehouse pest Callosobruchus chinensis (Coleoptera: Bruchidae). These pests can cause yield losses of up to 90%. Populations of adult C. chinensis have a close correlation in influencing the development of this pest in mung bean storage. This study aims to determine the correlation between the sex ratio of the population and its development in C. chinensis and to see its preference for mung beans. This research was conducted at the Plant Breeding Laboratory, Brawijaya University. The method was carried out by investing adult C. chinensis in mung beans based on the sex ratio, there are four sex ratio comparisons observed. Observations were made every week to see the number of eggs, larvaes, adults and dead insects. Based on the results of the study, the sex ratio of 2 males and 3 females resulted in the highest number of populations, a total of 72 eggs and 46 adult C. chinensis. Our hypothesis is that a high sex ratio leads to an increase in the population of C. chinensis. The vima variety is resistant mung beans compared to consumption varieties because it has lower seed weight loss. The results of this study are preliminary results that can be used for further research to evaluate the correlation between sex ratio, population and development of C. chinensis